Carving Economic Fortunes out of the Covid-19 Pandemic: The case of Entrepreneurialism in UK - Ofori, Felix Nana Kofi; Appiah, Kenneth; Gibson, Ammar (Archives of Business Research, 2023)
This article examines the interaction between the Covid-19 pandemic (pandemic) and entrepreneurship in the United Kingdom (UK). It contends that although the pandemic has obliterated several businesses and their concomitant partners throughout the world, particularly the UK, a new swathe of entrepreneurial activities have evolved to spur socio-economic ventures in stabilising the frontiers of society. The article also synthesises the dimensions critical for successful creation of entrepreneurship by exploring the effects of the pandemic, leadership, including the financial sector as key constituents in revving new ventures. Whilst weak institutions often induced corrupt practices to stifle enterprising initiatives, the article further argues that good leadership reposes confidence in a beleaguered society by motivating people to carve for themselves and community, economic fortunes stemming out of the crisis and destructions. Lastly, the article concludes that whilst there is a complimentary relationship between a country’s endowment and the rate of entrepreneurships springing up in the UK, the converse is the case in most developing countries in the south.